Some features of the territories in the breeding males of the intertidal blenny Lipophrys pholis (Pisces: Blenniidae) - Almada, Vítor Carvalho (2013)
In this paper we present data on the organization of the territories in males of Lipophrys pholis during the breeding season. Data were collected during high tides by skin- and scubadiving and during low tides by direct inspection of nests. Our study area was located at Arrébida, Portugal. The main results are: (i) The territories of the breeding males of this species are temporary, being established each breeding season, (ii) The guarding males stay in the nest holes with the egg masses while the tide is low and are subjected to several hours of emersion in each tidal cycle, (iii) Even when the nests are submerged the fishes stay inside the nest for an average of 92% of the time. All the activities performed outside the nest correspond to an average of 27 minutes per day. (iv) There was a low frequency of territorial intrusions. Conspecific intruders released a significantly higher frequency of agonistic responses than did Coryphoblennius galerita. (v) Removal experiments showed that vacated territories are not occupied by other males during the same breeding season, (vi) Without the presence of the guarding male the eggs are slowly destroyed by predation and infection, but some eggs can still survive and hatch up to five days after the removal of the parental male. The results are discussed in terms of the probable costs and benefits of breeding intertidally.